2013 Global Food Policy Report Berlin Launch Event - Fan, Shenggen (2014)
Presentation by Shenggen Fan, IFPRI Director General, at "Berlin Launch of IFPRI’s 2013 Global Food Policy Report" event. June 11, 2014 in Berlin, Germany. Event details at: https://www.ifpri.org/event/berlin-launch-ifpri-s-2013-global-food-policy-report